1982
DOI: 10.1128/aem.43.4.891-894.1982
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-linked immunosorbent assays for detection and quantitation of the entomocidal parasporal crystalline protein of Bacillus thuringiensis subspp. kurstaki and israelensis

Abstract: An enzyme-linked immunosorbent assay was used to detect and quantitate the parasporal crystal toxins of Bacillus thuringiensis subspp. kurstaki and israelensis. The assay method described is extremely sensitive, accurate, and highly specific. With this technique, crystalline insecticidal proteins from several subspecies of B. thuringiensis were compared. The dipteran crystal toxin produced by B. thuringiensis subsp. israelensis was shown to share few epitopes with the lepidopteran toxin from B. thuringiensis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…kurstaki antiserum to subsp. kurstaki crystal protein (Wie et at, 1984). Other authors have reported a similar lack of immunological cross-reactivity between subsp.…”
Section: The Molecular Genetics Of B Thuringiensissupporting
confidence: 57%
See 1 more Smart Citation
“…kurstaki antiserum to subsp. kurstaki crystal protein (Wie et at, 1984). Other authors have reported a similar lack of immunological cross-reactivity between subsp.…”
Section: The Molecular Genetics Of B Thuringiensissupporting
confidence: 57%
“…The results of several studies indicated that no significant immunological relationships existed between the mosquitocidal and lepidopteran-toxic crystal proteins. Wie et al (1982) reported that in both Ouchterlony double-diffusion gel analyses and by indirect ELISA, there was no cross-reaction between the two different crystal proteins. However, subsp.…”
Section: The Molecular Genetics Of B Thuringiensismentioning
confidence: 99%
“…The ,PGel (sodium dodecyl sulphate-polyacrylamide gel electrophoresis) assay (Brussock and Currier 1990) is not reliable for the toxicity assay because the denatured or inactivated toxin shows protein bands on the gel. The enzymelinked immunoassay can be carried out only in highly sophisticated laboratories (Wie et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate dilutions were made and assayed for B. thuringiensis subsp. israelensis 5-endotoxin with an enzyme-linked immunosorbent assay (ELISA) procedure (20). Similar procedures to evaluate the efficiency of encapsulation of solubilized toxin yielded erratic results due to inefficient recovery of the proteins from the micro-lipid droplets.…”
mentioning
confidence: 99%
“…Sample preparation and ELISA analyses for the B. thuringiensis subsp. israelensis 5-endotoxin were performed as described previously (20) with an antibody raised to the 25to 30-kilodalton crystal proteins.…”
mentioning
confidence: 99%